2013
DOI: 10.1007/s00280-013-2209-7
|View full text |Cite
|
Sign up to set email alerts
|

Validation of tumour models for use in anticancer nanomedicine evaluation: the EPR effect and cathepsin B-mediated drug release rate

Abstract: PurposeIntravenously (i.v.) administered nanomedicines have the potential for tumour targeting due to the enhanced permeability and retention (EPR) effect, but in vivo tumour models are rarely calibrated with respect to functional vascular permeability and/or mechanisms controlling intratumoural drug release. Here the effect of tumour type and tumour size on EPR-mediated tumour localisation and cathepsin B-mediated drug release was studied.MethodsEvans Blue (10 mg/kg) and an N-(2-hydroxypropyl)methacrylamide (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 34 publications
4
43
0
Order By: Relevance
“…Breast and ovarian cancer also showed high clinical responses to PDCs, which correlated well with high levels of cathepsins observed in these tumour types, and with reports indicating the presence of the EPR effect. This finding is in line with other studies [13,14] and in agreement with that concluded by others (e.g., [13]). Moreover, our study also suggests that careful patient selection, in the form of pre-screening for enzyme content and the EPR effect, would be a rational approach for the further development and clinical application of PDCs.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Breast and ovarian cancer also showed high clinical responses to PDCs, which correlated well with high levels of cathepsins observed in these tumour types, and with reports indicating the presence of the EPR effect. This finding is in line with other studies [13,14] and in agreement with that concluded by others (e.g., [13]). Moreover, our study also suggests that careful patient selection, in the form of pre-screening for enzyme content and the EPR effect, would be a rational approach for the further development and clinical application of PDCs.…”
Section: Discussionsupporting
confidence: 83%
“…This observation also correlates with a recent study on validation of the tumour models for EPR activity, where high drug accumulation has been reported for both large and small lung tumours, and a low drug accumulation has been reported for the large breast tumours [13]. Disparities observed across the various studies are might be due to the heterogeneity within and between the tumour types (size and histological differences) and the diversity of the nanopharmaceutical characteristics [14].…”
Section: Magnitude Of the Epr Effect In Different Tumour Typessupporting
confidence: 70%
See 3 more Smart Citations